(untitled) (Marketing Journal, 2025)
This article analyzes strategies for using neuromarketing in the fashion industry. Neuromarketing aims to study consumersʼ subconscious emotions and influence their purchasing decisions. The research examines psychological, social, marketing, and technolog ical factors, exploring the mechanisms through which neuromarketing tools impact customer behavior. Additionally, the effectiveness of using visual, sensory, and cognitive stimuli in the fast fashion sector is discussed. The findings can be used to identif y key factors for conducting further neuromarketing research.